The Role of Proactive Personality to Explaining the Effect of Perceived Organizational Support and Empowering Leadership on Employee Voice - Yulidha, Annisa' Elma; Fajrianthi, Fajrianthi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Employee Voice as a constructive expression for organizations has become a big concern. Various studies were conducted to find the antecedents and consequences of employee voice. Perceived organizational support and empowering leadership offer a positive impact on employee behavior towards the organization. Various studies also attempt to examine the individual characteristics that lead to employee voice. Voice is expressed in the form of promotive and prohibitive behavior. The different forms of employee voice have attracted the attention of various researchers for further study. To continue several suggestions from previous research, this research measures the influence of Perceived Organizational Support and Empowering Leadership on both forms of Employee Voice with Proactive Personality as a moderator. The sample used was 145 employees in Indonesia with various company backgrounds. Data collection tool in the form of a questionnaire using a scale of Perceived Organizational Support with reliability 0,90; Empowering Leadership questionnaire with reliability 0,829; Promotive Voice with reliability 0,91; Prohibitive Voice with reliability 0.91; Proactive Personality with reliability 0,899. Data analysis uses partial least square with the help of SmartPLS 4.0. The results of this research indicate that Proactive Personality plays a role in explaining the influence of Perceived Organizational Support on Employee Voice (Promotive Voice). However, it does not moderate the effect of perceived organizational support on Prohibitive Voice, and it does not moderate the effect of Proactive Personality on Employee Voice. So, it can be concluded that proactive individuals with high Perceived Organizational Support will be more likely to voice their suggestions and ideas than those who are passive or less proactive.Employee Voice sebagai ekspresi konstruktif yang berharga bagi oranisasi telah menjadi perhatian besar. Berbagai penelitian dilakukan untuk menemukan anteseden dan konsekuensi yang dihasilkan employee voice. Perceived organizational support dan empowering leadership menawarkan dampak yang positif pada perilaku karyawan terhadap organisasi. Berbagai penelitian juga berusaha melihat karakteristik individu yang mengarahkan pada keterlibatan dalam employe voice. Voice diekspresikan dalam bentuk perilaku promotive dan prohibitive. Perbedaan bentuk employee voice menarik perhatian berbagai peneliti untuk ditelaah lebih lanjut. Untuk menindaklanjuti penelitian sebelumnya, maka pelitian ini mengukur pengaruh Perceived Organizational Support dan Empowering Leadership terhadap kedua bentuk Employee Voice dengan Proactive Personality sebagai moderator. Sampel yang digunakan adalah 145 karyawan di Indonesia yang bekerja di berbagai latarbelakang perusahaan dengan teknik sampling yang digunakan yakni convenience sampling. Alat pengumpulan data berupa kuesioner menggunakan skala survey of Perceived Organizational Support dengan reliabilitas 0,90; Empowering Leadership questionnaire dengan reliabilitas 0,829; Promotive Voice denan reliabilitas 0,91 dan Prohibitive Voice dengan reliabilitas 0.91; proacive personality dengan reliabilitas 0,899. Analisis data menggunakan partial least square dengan bantuan SmartPLS 4.0. Hasil penelitian ini menunjukkan bahwa Proactive Personality berperan dalam menjelaskan pengaruh Perceived Organizational Support terhadap Employee Voice (Promotive Voice). Namun tidak memoderasi pengaruh perceive organizational support terhadap Prohibitive Voice, dan tidak memoderasi pengaruh Proactive Personality terhadap Employee Voice. Sehingga dapat disimpulkan bahwa individu yang proaktif dengan Perceived Organizational Support yang tinggi akan lebih menyuarakan saran dan ide mereka daripada mereka yang pasif atau kurang proaktif.